Answer to Question #233764 in Differential Equations for Shamim

Question #233764

z=a(x+y)+b


1
Expert's answer
2021-09-07T03:13:03-0400

This question is incomplete but we can treat this as a problem of elimination of the arbitrary constant.

"z=a(x+y)+b...(1)\n\\\\"

Differentiating (1) with respect to "x, y" , we get

"p=\\frac{\\partial z}{\\partial x}=\\frac{\\partial (a(x+y)+b)}{\\partial x}=a...(2)\n\\\\p=\\frac{\\partial z}{\\partial y}=\\frac{\\partial (a(x+y)+b)}{\\partial y}=a...(3)"

Now, subtracting (3) from (2), we get

"p-q=0"


Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog